CYTODIAGNOSIS OF MUCINOUS CYSTADENOCARCINOMA OF RENAL PELVIS - A RARE CASE REPORT - BHARATHI. K; ANURADHA S; ABDUL KHALIQUE (International Journal of Pharma and Bio Sciences, 2012)
Primary mucinous adenocarcinoma of renal pelvis is a rare cystic neoplasm which mimics a hydronephrosis or pyonephrosis radiologically. We are presenting here a case report where mucinous cystadenocarcinoma of pelvicalyceal system was mimicking clinically and radiologically as pyonephrosis but diagnosed preoperatively through a simple and rapid test, Ultrasound- guided fine-needle aspiration cytology. Cytology smears revealed signet ring like malignant epithelial cells in a mucinous background. A cytological diagnosis of mucinous adenocarcinoma of renal pelvis was suggested. It is essential to diagnose mucinous cystadenocarcinoma preoperatively through cytology to decide the appropriate surgical plan. Radical nephrectomy with partial ureterectomy was done. Grossly the entire kidney was converted into thick walled cyst measuring 20 × 16 cm containing thick mucinous material. Histopathological examination confirmed the cytological diagnosis. The post operative period was uneventful and one year follow up showed no recurrence. Thus a timely cytological diagnosis made preoperatively saved the patients life.